1993
DOI: 10.3168/jds.s0022-0302(93)77596-7
|View full text |Cite
|
Sign up to set email alerts
|

Blood Polymorphonuclear Leukocyte Chemotaxis During Experimental Escherichia coli Bovine Mastitis

Abstract: The relationship between the severity of experimental Escherichia coli mastitis and the chemotactic response of blood polymorphonuclear leukocytes was investigated before and during mastitis. Experimental E. coli mastitis was induced in 10 healthy cows by inoculation of the rear right quarters with I d cfu of E. coli. Cows were classified into two groups based on the severity of the mastitis. Bacterial growth in the inoculated quarter was used as parameter that indicated severity.Before and during experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…During the first stages of experimental mastitis, the chemotactic response of leukocytes decreased in both, moderately and severely infected animals. The recovery of the chemotactic response of the leukocytes occurred more rapidly in moderately than in severely diseased cows [124]. It has been observed that early after challenge phagocytosis decreases in circulating PMN, but the initial decrease occurred faster in severely affected cows.…”
Section: Circulating Leukocytesmentioning
confidence: 97%
See 2 more Smart Citations
“…During the first stages of experimental mastitis, the chemotactic response of leukocytes decreased in both, moderately and severely infected animals. The recovery of the chemotactic response of the leukocytes occurred more rapidly in moderately than in severely diseased cows [124]. It has been observed that early after challenge phagocytosis decreases in circulating PMN, but the initial decrease occurred faster in severely affected cows.…”
Section: Circulating Leukocytesmentioning
confidence: 97%
“…The sporadic detection of limited LPS amounts in plasma contrasts with the massive LPS amounts that are released in the mammary gland during E. coli mastitis [246]. In the LPS model, the inflammatory reaction is induced by "bolus injection"; in the E. coli infection model, LPS is released during several hours [64,93,97,124,161,167,210,244,245]. Most LPS mastitis models described in literature are performed after peak lactation.…”
Section: Endotoxin As Systemic Mediatormentioning
confidence: 99%
See 1 more Smart Citation
“…Kehrli et al (1989) hypothesized that an immunosuppression may occur during the periparturient period and therefore predisposes the dairy cow to new infections. Several of the altered neutrophil functions were found to be related to the severity of experimentally induced Escherichia coli mastitis during early lactation Lohuis et al, 1990;Kremer et al, 1993;Van Werven et al, 1997). The number of leukocytes prior to infection was also decreased.…”
Section: Introductionmentioning
confidence: 98%
“…Impaired PMNL chemotaxis has been shown to lead to a more severe disease status (Van Werven et al, 1997). During experimentally induced Escherichia coli mastitis in cows, the capability of PMNL to respond to chemotactic stimuli has been shown to relate negatively to the outcome of the disease (Kremer et al, 1993). Following acute infection, a decrease in L-selectin expression on peripheral blood PMNL was reported (Diez Fraile et al, 2003) and was accompanied by a concomitant leukopenia and shift in the circulating PMNL pool from mature to immature forms (Heyneman et al, 1990;Van Oostveldt et al, 2002).…”
Section: Introductionmentioning
confidence: 99%